Necrotizing fasciitis. Updating on the topic - Yovanny Ferrer Lozano; Yanett Morejón Trofimova (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Necrotizing lesions in soft tissues are a heterogeneous type of illnesses. infrequent but potentially fatal, characterized by skin infection, of the subcutaneous tissue and muscle. Necrotizing fasciitis is an unsual disease. There no incidence studies in Cuba. Its etiology is generally polymicrobial. Streptococcus pyogenes is the most frequent germ. Bacterial toxins, through its cytopathic and thrombotic activity, are responsible of tissue necrosis. Its clinical development is not uniform, doctor only achieve an initial correct diagnosis in the 15 to 30 % of the cases. If initial sings and symptoms are identified its mortality may be reduced to 12%. The objective of this work is to review the topic and present the current diagnosis and treatment criteria.